Efektivitas Media Pembelajaran terintegrasi Augmented Reality Materi Asam Basa Fase F terhadap Hasil Belajar Peserta Didik di SMA Negeri 13 Padang - Rahmad Adi Putra; Nofri Yuhelman; Guspatni (LPPM Universitas Negeri Jakarta, 2025)
This study aims to determine the effectiveness of acid-base learning media integrated with Augmented Reality (AR) technology on improving students' cognitive learning outcomes. One of the topics discussed in chemistry learning is acid-base material. Given the concept of acid-base is abstract, it requires visualization in three-dimensional form to facilitate understanding. The learning media used has gone through validity and practicality tests, with results showing that the media is valid and practical. This research is included in the pre-experimental type with a one group pretest-posttest design. The research sample consisted of 35 students of class F.6 at SMA Negeri 13 Padang. The instrument used was a multiple choice diagnostic test. Data analysis obtained that the data is normally distributed with a Wcount value of (0.93443) which is greater than Wtable (0.934). Hypothesis testing using paired sample t-test shows that the tcount of (21.23) is greater than the ttable of (2.03011). Thus, it can be concluded that the use of Augmented Reality-based learning media on acid-base material is effective in improving the learning outcomes of students at the SMA / MA phase F level Keywords: Effectiveness, Learning Media, Augmented Reality, Acid-Base, Learning Outcomes